Compensation disclosures and strategic commitment: Evidence from revenue-based pay - Bloomfield, Matthew J. (Journal of Financial Economics, 2021)
A 2006 rule change in the United States mandated that publicly traded firms provide more detailed disclosures about executives’ compensation plans. In response to the new disclosure requirements, Cournot firms with large market shares add revenue-based pay to their CEOs’ pay packages. This change in pay practices coincides with a shift towards more aggressive product market equilibria, characterized by greater production expenditures and lower margins. Jointly, these patterns are consistent with predictions from the theory of “strategic delegation,” and suggest that the new disclosure requirements enhanced the viability of committing through executive incentives. After adopting the new disclosure requirements, many firms appear to restructure their executives’ pay packages as strategic devices designed to make rivals curtail their competitive actions.